Please help me differentiate the following equations: g(x)=e^(x)ln(x^4) x^5ln(x-1/3x^(3)) f(x)=(3x^(2)-6x+6)e^(x) f(x)=x^(5)e^(10x) Thanks!
Follow Math Help Forum on Facebook and Google+
Originally Posted by TaylorGold Please help me differentiate the following equations: g(x)=e^(x)ln(x^4) x^5ln(x-1/3x^(3)) f(x)=(3x^(2)-6x+6)e^(x) f(x)=x^(5)e^(10x) Thanks! In each case you have to use the product rule. Please show your work and say where you get stuck.
Originally Posted by TaylorGold Please help me differentiate the following equations: g(x)=e^(x)ln(x^4) x^5ln(x-1/3x^(3)) f(x)=(3x^(2)-6x+6)e^(x) f(x)=x^(5)e^(10x) Thanks! Originally Posted by mr fantastic In each case you have to use the product rule. Please show your work and say where you get stuck. And in a number of cases the chain rule. CB
View Tag Cloud